Brain changes with Chinese reading development in typical and atypical readers - Cao, Fan (Frontiers in Psychology, 2023)
Reading is a high-order cognitive process that is unique in human beings. There is a prolonged developmental course and a wide range of proficiency levels associated with reading. In this review, I focus on brain changes underlying Chinese reading development in both typical readers and readers with reading disability. Reading development in typical readers is characterized by a shift from dorsal phonological reading to ventral orthographic reading in the brain and increased interactive specialization in the reading network. Even though some individuals with reading disability may be able to catch up with typical readers on phonological reading by adulthood, they cannot reach fluent orthographic reading. In the brain, the reduction of brain activation in the left inferior frontal gyrus associated with reading disability disappears by adulthood, suggesting that this is a developmental delay, while there is a greater reduction of brain activation in the left inferior temporal gyrus in adults than children with reading disability. It suggests a greater deficit in the dorsal phonological reading pathway in children and a greater deficit in the ventral orthographic reading pathway in adults with reading disability. This review provides insights about the developmental trajectories in typical and atypical reading.